Crack cause analysis of a graphite nozzle throat insert. (August 2017) - Sun, Lin; Bao, Futing; Zhao, Yu; Hou, Lian; Hui, Weihua; Zhang, Ning; Shi, Wei
Abstract: With an objective to determine the failure cause of a throughout crack at an angle of 45° and a breach during a firing test, a simplified analysis procedure with consideration of the structure gap was established to simulate the thermo-structural response of a nozzle. By neglecting erosion and pyrolysis of the insulating materials and establishing temperature-dependent or anisotropic material models, ANSYS Parameter Design Language codes were written to perform the fully coupled thermal-structural simulation. A Quasi-1D flow was calculated for supplying boundary conditions. Study on mesh independence and time step independence was also conducted to evaluate simulated results. It was found that shortly after ignition, compressive stress in the x direction and tensile stress in the y direction contributed to anomalies. And through contact status analysis, inappropriate gap design was regarded as the origin of the too large stress, which was the primary cause of these anomalies during firing test. Simulation results were in good agreement with firing test results. In addition, the simplified analysis procedure was proven effective. Gap size should be seriously dealt with in the future design.